SEPTOPLASTIC IN CHILDREN - T.A. Polunina; M.M. Polunin (Union of pediatricians of Russia, 2011)
The article highlights the issues of treatment of children, observed with a diagnosis of «Contortion of nasal septum». The authors recommend deep examination of patients with this disease (ENT examination, performance of endoscopic examination, computed tomography, rhinomanometry) to work out the therapy adequate to present changes. After the diagnosis has been precised, all children had septoplastic, but if necessary, at one time with it they also underwent to rhinoplastic, lower turbinates vasosection, bullosa modified medium turbinates correction. If decongestants were necessary, we used xylometazon to reduce swelling of the nasal mucosa. It in addition to α2-adrenoceptor agonists contains moisturizing ingredients to prevent mucous membranes dryness. Key words: curvature of the nasal septum, examination, treatment, rhinoplastic, septoplastc, vasosection, children. (Pediatric Pharmacology. - 2011; 8 (5): 46-48.)